2021
DOI: 10.1371/journal.pone.0259253
|View full text |Cite
|
Sign up to set email alerts
|

Association between personality traits and food stockpiling for disaster

Abstract: This study investigated the association between personality traits and food stockpiling for disasters in predicted high-risk areas of food shortages due to the Nankai Trough Earthquake. This survey was conducted between December 18 and 20, 2019, using a web-based questionnaire. The participants were 1,200 individuals registered with an online survey company. This study analyzed the association between the Big Five personality traits and food stockpiling status (n = 1192). The Big Five personality traits assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The "utilization of Japanese Space Food as Japan Disaster Food" is expected to increase the number of "main and/or side dishes" of Japan Disaster Food products. In addition, the Ministry of Agriculture, Forestry and Fisheries' Food Stock Guide for Disasters states that it is desirable to stockpile food for 3-7 days at home (2). The application of space food to disaster foods will lead to "exciting disaster-prevention stockpiling" and can be expected to raise interest in and awareness of disaster-prevention stockpiling (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "utilization of Japanese Space Food as Japan Disaster Food" is expected to increase the number of "main and/or side dishes" of Japan Disaster Food products. In addition, the Ministry of Agriculture, Forestry and Fisheries' Food Stock Guide for Disasters states that it is desirable to stockpile food for 3-7 days at home (2). The application of space food to disaster foods will lead to "exciting disaster-prevention stockpiling" and can be expected to raise interest in and awareness of disaster-prevention stockpiling (28).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the need for food stockpiling has increased due to the frequent occurrence of natural disasters and pandemics (1,2). In disaster-stricken areas, in the context of the stress of enforced gathered life and inadequate lifelines, such as electricity and gas, disaster-related foods are indispensable for nutrition to prevent disaster-related deaths.…”
mentioning
confidence: 99%
“…Each trait measure consists of two items and participants rated each item on a scale of 1 (strongly disagree) to 7 (strongly agree). The total score for each trait was calculated as described in a previous study [ 29 , 30 , 31 ]. The assessment was conducted before joint go and no-go tasks.…”
Section: Methodsmentioning
confidence: 99%
“…In face of existential and resource threats, some individuals may be more likely to use consumption as a coping mechanism than others [6,12,34]. Accordingly, research during the early phases of the COVID-19 pandemic has shown that a myriad of individual and cultural factors can influence stockpiling: personality [35], high avoidance of uncertainty [36], individualism [36,37], and inability to tolerate stress [38]. In addition to these factors, individual differences in childhood SES [39] might also impact stockpiling tendencies during the COVID-19 pandemic because one's childhood SES has been shown to influence behavior during uncertain situations such as economic recessions and situations that render mortality cues salient [6][7][8].…”
Section: Individual Differences In Stockpiling Behaviormentioning
confidence: 99%